Exploring the Association between Periodontitis and Erectile Dysfunction: A Systematic Review - Ridho, Fiki Muhammad; Agustina, Arista Widya; Hidayati, Novi Nurul; Pratama, M. Ilham; Laksono, Eko Puji (Indonesian Andrology and Biomedical Journal, 2024)
Background: Periodontitis (PD) remains a global public health problem. Evidence revealed that PD contributes to the development of systemic diseases, including effects on men's sexual health such as erectile dysfunction (ED). Objective: To review and explore the association between PD and ED. Methods: Following PRISMA guidelines, a systematic review of studies published in Scopus, PubMed, ScienceDirect, and Google Scholar was conducted. A comprehensive literature search until February 2024 by combining several keywords and applying eligibility criteria was performed. JBI critical appraisal checklist was employed for quality assessment. Results: A total of 15 studies involving 216,753 subjects were included. Of the 15 studies, 13 of them demonstrated a significant association between PD and ED, the other two did not. Only one study included examination of hormonal and biochemical levels. Also, one study revealed that periodontal treatment was significantly associated with improving ED. Summary: According to the findings, a significant association between PD and ED is evident. It is believed that the inflammatory processes associated with PD contributes to the emergence of ED, yet the exact underlying mechanism remains unclear. The scarcity of research and the complexity of the association between PD and ED suggest that future rigorous studies should be conducted. Additionally, dentists and general practitioners must be aware of the interconnection between these diseases, enabling them to provide comprehensive education to patients, particularly concerning the prevention and management of periodontal disease.